Dietary Shifts May Trigger Dysbiosis and Mucous Stools in Giant Pandas (Ailuropoda melanoleuca) - Williams, Candace L.; Dill-McFarland, Kimberly A.; Vandewege, Michael W.; Sparks, Darrell L.; Willard, Scott T.; Kouba, Andrew J.; Suen, Garret; Brown, Ashli E. (Frontiers in Microbiology, 2016)
Dietary shifts can result in dysbiosis between the host and its gastrointestinal tract (GIT) microbiota, leading to negative outcomes including inflammation. Giant pandas (Ailuropoda melanoleuca) are physiologically classified as carnivores; however, they consume a herbivorous diet with dramatic seasonal feeding shifts and episodes of chronic GIT distress with symptoms including abdominal pain, loss of appetite and the excretion of mucous stools (mucoids). These episodes adversely affect the overall nutritional and health status of giant pandas. Here, we examined the fecal microbiota of two giant pandas’ normal and mucoid stools and compared these microbiota to baseline samples from a season with historically few episodes. To identify the microbiota present, we isolated and sequenced 16S rRNA using next-generation sequencing. Mucoids occurred following a seasonal feeding switch from predominately bamboo culm (stalk) to leaves. All fecal samples displayed low diversity and were dominated by bacterial in the phyla Firmicutes and to a lesser extent, the Proteobacteria. Fecal samples immediately prior to mucoid episodes had lower microbial diversity compared to baseline samples, followed by increased diversity in mucoids. Mucoids were mostly comprised of common mucosal-associated taxa including Streptococcus and Leuconostoc species, and exhibited increased abundance for bacteria in the family Pasteurellaceae. Taken together, these findings indicate that diet-induced intestinal dysbiosis in giant pandas likely results in an expulsion of the mucosal lining in the form of mucoids. We suggest that these occurrences serve to reset their GIT microbiota, as giant pandas have retained a carnivorous GIT anatomy while shifting to an herbivorous diet.